COHESIVE DEVICES IN DONALD TRUMP’S FIRST SPEECH AS THE AMERICAN PRESIDENT - Rahman, Rezi Fauzi; Firdaus, Dadan; Ardiansyah, Erlan Aditya (Universitas Islam Negeri Sunan Gunung Djati, 2023)
The presence of cohesive devices in speech plays a crucial role in representing the functioning of language. Beyond enhancing the effectiveness of written communication, cohesive devices guide listeners into the realm of context, fostering a shared understanding of meaning. This research focuses on analyzing grammatical and lexical cohesions in Donald Trump's inauguration speech from the 2016 United States presidential election, which took place on January 20th, 2017. The objective of the study is to explore the representation of both grammatical and lexical cohesions. A qualitative method was employed, and data were extracted from pauses in Trump's speech, specifically noting cohesive devices. The findings reveal that grammatical cohesion encompasses references, substitutions, ellipsis, and conjunctions. Lexical cohesions identified include repetition, synonymy, antonymy, hyponymy, meronymy, and collocation. Repetition was observed in 29 pauses, substitutions in 6 pauses, ellipsis in 8 pauses, and conjunctions in 31 pauses. Regarding lexical cohesion, the study identified repetition in 32 pauses, synonymy in 10 pauses, antonymy in 5 pauses, hyponymy in 3 pauses, meronymy in 2 pauses, and collocation in 6 pauses. However, it was noted that incohesive instances occurred in the case of conjunctions, potentially influenced by the situational or contextual factors. In conclusion, this study sheds light on the diverse cohesive devices employed in Trump's inauguration speech, emphasizing the significance of context in understanding language use. Keywords: cohesive device, conjunctions, ellipsis, grammatical cohesion, lexical cohesion, substitutions